Poverty reduction and digitalization in Indonesia: The conditional role of human capital and economic growth in an underdeveloped province - Wurarah, Rully Novie; Sangadji, Maryam; Awom, Sarce Babra (Asian Journal of Economic Modelling, 2025)
The purpose of this study is to explore how human capital could help close the digital divide in Indonesian areas currently under development. Digitalization is proxied by MSMEs actively using e-commerce platforms (≥ transactions/month), sourced from the Ministry of Communication and Informatics. Using panel data from the 10 provinces with the lowest human development index (HDI) in Indonesia from 2019 to 2023, we contrast the efficiency of digitalization with conventional development drivers. Spatial econometrics analysis confirms significant poverty spillovers across contiguous provinces (ρ=0.22; p < 0.01), indicating that local poverty dynamics are interlinked with neighboring regions. Fixed-effects panel regression and spatial econometrics analysis reveal statistically significant inverse associations between the Human Development Index (HDI) and poverty. Digitalization significantly reduces poverty only after HDI exceeds a threshold of 65 (β= -0.133; p < 0.05), confirming the critical role of human capital as a prerequisite. This study has practical implications, showing that the equally crucial expenditures in education, healthcare, and community capacity building contribute to closing the digital divide in Indonesia because digital inclusion depends on human capital. The phased strategy proposed emphasizes human capital as the fundamental component of efficient digital integration, supporting the philosophy of inclusive development.